2012
DOI: 10.1139/g2012-064
|View full text |Cite
|
Sign up to set email alerts
|

Construction and analysis of an SSH cDNA library of early heat-induced genes ofVigna aconitifoliavariety RMO-40

Abstract: Moth bean ( Vigna aconitifolia (Jacq.) Marechal) is an important grain legume crop grown in rain fed areas of hot desert regions of Thar, India, under scorching sun rays with very little supplementation of water. An SSH cDNA library was generated from leaf tissues of V. aconitifolia var. RMO-40 exposed to an elevated temperature of 42 °C for 5 min to identify early-induced genes. A total of 488 unigenes (114 contigs and 374 singletons) were derived by cluster assembly and sequence alignment of 738 ESTs; out o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…In the current study, VaDJI was isolated from Vigna using an SSR cDNA library and was found to be induced by signalling molecules and abiotic stress treatments ( Rampuria et al., 2012 ). DnaJ proteins are known to be induced by heat, intense light, cold, methyl viologen (MV) and to play roles in signal transduction, development and stress tolerance ( Xia et al., 2014 ; Lee et al., 2018 ; Rampuria et al., 2018 ; Wang et al., 2018a ; Wang et al., 2019a ; Wang et al., 2020 ; Li et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the current study, VaDJI was isolated from Vigna using an SSR cDNA library and was found to be induced by signalling molecules and abiotic stress treatments ( Rampuria et al., 2012 ). DnaJ proteins are known to be induced by heat, intense light, cold, methyl viologen (MV) and to play roles in signal transduction, development and stress tolerance ( Xia et al., 2014 ; Lee et al., 2018 ; Rampuria et al., 2018 ; Wang et al., 2018a ; Wang et al., 2019a ; Wang et al., 2020 ; Li et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The full-length VaDJI CDS sequence was amplified from Vigna aconitifolia (RMO-40) using gene-specific primers listed in the earlier cDNA-AFLP study ( Rampuria et al., 2012 ). The PCR product of VaDJI was cloned into a pRT100 vector expression cassette using Apa I and Kpn I restriction sites at the 5′/3′ end of the sequence ( Gautam et al., 2019 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4,15 The expression of genes for abiotic stress responsiveness was carried out by various gene expression studies in legumes. 3,13,16 Similarly, in the present study, the expression characterization of selected genes was done by semi-qRT PCR analysis. This was done to select the gene which shows the exponential up-regulation during the time course experiment of drought in moth bean.…”
Section: Assessment Of Drought Stress-responsive Expression Of Moth B...mentioning
confidence: 98%
“…The functional genomic approaches such as genome wide association studies (GWAS) and gene expression profiling using microarrays can catalyse the discovery of novel genes associated to heat stress 68 . In addition, suppression subtractive hybridization (SSH) is another effective and productive technique used for the screening and cloning of the genes/ESTs that express differentially under heat stress 9, 10 . Reverse genetic techniques can improve the understanding of their expression patterns under heat stress.…”
Section: Introductionmentioning
confidence: 99%